Implemetation of Environmental Care through Gotong Royong Activities in Early Childhood Education Institutions - Hamidatun Annafi'u Yurintama (Kumara Cendekia, 2026)
Early childhood education plays a crucial role in instilling character values, including environmental awareness. These values need to be instilled through direct experience so that children can understand the meaning of their behavior. This study aims to describe the implementation of environmental awareness values through mutual cooperation activities in early childhood. This study used a qualitative approach with a descriptive research type. The research subjects included the principal, teachers, and children involved in the mutual cooperation activities. Data collection techniques were carried out through observation, interviews, and documentation. Data were analyzed using the Miles and Huberman interactive analysis model, which includes data reduction, data presentation, and conclusion drawing. The results showed that mutual cooperation activities were carried out routinely on Fridays or Saturdays in the first and third weeks of each month, and were also carried out flexibly at certain times when needed by involving children in various cleaning activities such as sweeping the yard, pulling weeds, and collecting trash. These activities not only maintain the cleanliness of the school environment but also foster an attitude of responsibility, cooperation, and concern for the environment. Habituation through direct experience and teacher role models as behavioral models has been proven to help children understand the importance of maintaining environmental cleanliness from an early age.